Discretionary behavior and performance in educational organizations the missing link in educational leadership and management - Duyer, Ibrahim; Normore, Anthony H. (Advances in educational administration ;, 2012)
The purpose of this volume is to contribute for the development of a parsimonious and coherent theory/understanding in discretionary behavior in organizations, educational organizations in particular. The volume will set a stage for the discussion of significance and timeliness of discretionary behavior towards solving long lasting issues in educational organizations. The volume also will create an environment where the future discourse and direction of discretionary behavior in educational organizations are discussed.